Virtuous waters : mineral springs, bathing, and infrastructure in Mexico - Walsh, Casey (University of California Press, 2018)
"Virtuous Waters is the first study of mineral waters and bathing in Mexico. It traces the evolving ideas about these waters, from European contact to the present, in order to shed new light on human-environment relations in the modern world. Our relation to water is among the most urgent of global issues, as increasing scarcity and pollution threaten food shortages, deteriorating public health, and the collapse of aquatic ecosystems. Drawing on ideas from political ecology, the author brings together an analysis of the shifts in the concept of water and a material history of environments, infrastructures, and bathing. The book analyzes a range of issues concerning complex "water cultures" that have formed around Mexican groundwaters over time and suggests that this understanding might also help us comprehend and confront the water crisis that is coming to a head in the twenty-first century"--Provided by publisher